El sentido en la perspectiva de Luhmann: entre una definición formal y su puesta en forma - Bialakowsky, Alejandro (2016)
This article analyzes the theoretical and epistemological elaborations of Luhmann about the problem of meaning. Its aim is to trace the key tension that crosses the different inflections of his proposal: between a formal definition of meaning, with the distinction of selective actuality and the horizon of potentialities, and its taking form, parting from the operations of systems. In order to do this, three decisive moments of his perspective are studied. First, the article focuses on his claim to formally conceptualize and to «desubjectivize» meaning, within a series of theoretical inheritances and ruptures.Second, it analyzes the consequences of his autopoietical proposal, either by pointing out meaning as the coevolutionary achievement of psychic and social systems, or in its analysis of the linguistic generalization of meaning. Third, in his later works, with the intensification of his theory of the observer, the article examines his approach to meaning from the distinction between medium and form. Finally, the previous considerations are combined with his theory of evolution and differentiation of society, from which the article reflects on the particularities of the conceptual construction of Luhmann about meaning.